Morphometric analysis of cervical vertebrae with multidetector computerized tomography (Annals of Medical Research, 2021)
Aim: We aimed to present some morphometric values ​​of the cervical vertebra in our study.Materials and Methods: The study was performed on 100 individuals (50 females-50 males) aged between 20 and 80 years with multidetector computed tomography and cervical vertebrae. Parameters are measured and recorded in our work; sagittal diameter of foramen vertebra, transverse diameter of foramen vertebra, sagittal diameter of corpus vertebra, transverse diameter of corpus vertebra and corpus vertebra height.Findings: We investigated whether there was a statistically significant difference between men and women. Sagittal diameter of corpus vertebra and transverse diameter of corpus vertebra values ​​were significantly higher in all cervical vertebrae than in females (p0.05). Corpus vertebrae height values were significantly higher (p0.05) in men except C2 vertebrae.Conclusion: As a result, the averages we obtained are important in terms of creating reference values ​​in Turkish society. We think that these values ​​will help radiologists for diagnosis and surgeons for surgical interventions.Keywords: Vertebra; morphometry; anatomy.